Dewan Perwakilan Daerah dalam Sistem Ketatanegaraan Indonesian: Studi Sistem Bikameral - Raden Siti Rachmah Wardani (CV. Social Politic Genius (SIGn), 2023)
This study aims to examine and analyze the authority of the DPD in the law-forming process based on the bicameral system. This study uses normative legal research with the statute and comparative approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that the DPD members possess strong political legitimacy, because members of both chambers within the legislative branch are elected through the electoral process in Indonesia. However, no provision in the legislation grants the DPD a legislative function. Instead, the DPD holds limited authority in the law-forming process, only able to propose, participate in discussions, and provide considerations to the DPR over draft laws. In comparison, Indonesia’s DPD has significantly more limited authority than senates in other countries with bicameral systems. Additionally, several perspectives, paradigms, and differentiating factors help explain the reasons and objectives behind implementing bicameral systems. Therefore, it is recommended that stakeholders understand the various perspectives, paradigms, and differentiating factors that explain the reasons and objectives behind implementing bicameral systems in other countries. This understanding aims to enhance the authority of the DPD as a legislative power within the Indonesian state governance system. This understanding can also serve as a consideration for stakeholders in amending the 1945 Constitution, Law Number 17 of 2014, and Law Number 12 of 2011. In this context, the legislative function in a bicameral system refers to forming and ratifying laws by both chambers within the legislative branch. Consequently, Indonesia’s bicameral system can become more effective, responsive, and inclusive, ultimately promoting a more democratic and stable state governance system in the future.